An Overview on Blockchain (International Journal of Innovative Research in Computer Science & Technology, 2021)
Blockchain is a decentralized technology.  When it comes to resolving business issues, it wields  considerable power. Every transaction on the blockchain is  encrypted, and each transaction is linked to a previous  transaction or record. Blockchain transactions are validated  by algorithms running on nodes. A single entity cannot start  a transaction. Eventually, blockchain provides transparency  by allowing any participant to view transactions at any  moment. Smart contracts provide secure transactions,  minimizing the risk of third-party interruptions. Ethereum is  a decentralized platform based on smart contracts. It enables  developers to create markets that transfer money according  to the instructions given years ago. Blockchain is  distinguished by two key characteristics: immutability and  decentralization. Deals are completed faster; Transactions  and authentication are completed in a matter of seconds, and  much more.
Keywords: Blockchain; Cryptocurrency; Ledger; Network; Transaction